Case 3686: Bulimus rupestris Philippi, 1836 (Gastropoda, Stylommatophora, Chondrinidae): proposed conservation of the specific name - Balashov, Igor; Welter-Schultes, Francisco (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Article 23.9.5 of the Code, is to conserve the specific name of the terrestrial snail Bulimus rupestris Philippi, 1836 (currently Rupestrella rupestris, Chondrinidae), originally published as a junior primary homonym of Bulimus rupestris Krynicki, 1833 (currently classified in the genus Peristoma, Enidae) by ruling under the plenary power to disregard their primary homonymy.
Keywords: Nomenclature; taxonomy; Gastropoda; Stylommatophora; Chondrinidae; Enidae; Bulimus; Rupestrella; Peristoma; Bulimus rupestris; Rupestrella rupestris; Peristoma rupestre; terrestrial snail; Europe